2020
DOI: 10.3389/fphar.2020.00868
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Based Pharmacokinetic Modeling of Monoclonal Antibodies in Pediatric Populations Using PK-Sim

Abstract: Physiologically based pharmacokinetic (PBPK) models are increasingly used to support pediatric dose selection for small molecule drugs. In contrast, only a few pediatric PBPK models for therapeutic antibodies have been published recently, and the knowledge on the maturation of the processes relevant for antibody pharmacokinetics (PK) is limited compared to small molecules. The aim of this study was, thus, to evaluate predictions from antibody PBPK models for children which were scaled from PBPK models for adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 46 publications
3
34
0
Order By: Relevance
“…Taken together, our comprehensive analysis demonstrated that an mPBPK model is a reasonable choice for prediction of clearance of therapeutic proteins in children. Model elaboration with more assumption and inclusion of several unknown parameters (eg, ontogeny of neonatal Fc receptor) did not practically improve the predictive performance of PBPK models 17,23,27–29 …”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Taken together, our comprehensive analysis demonstrated that an mPBPK model is a reasonable choice for prediction of clearance of therapeutic proteins in children. Model elaboration with more assumption and inclusion of several unknown parameters (eg, ontogeny of neonatal Fc receptor) did not practically improve the predictive performance of PBPK models 17,23,27–29 …”
Section: Discussionmentioning
confidence: 96%
“…So far, few whole‐body PBPK or mPBPK models for therapeutic proteins have been evaluated for prediction of PK in children 17,23,27–29 . In 2 studies, Malik and Edginton 17,28 showed that the concentrations of monoclonal antibodies (infliximab, pagibaximab, palivizumab, and MEDI8897) were predicted within a 0.5‐ to 2‐fold error for 67% to 93% of the observations using a whole‐body PBPK model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many early studies focussed on a potential role for TDM-guided KI dosing, however, sufficient evidence has yet to be generated to support widespread implementation for any KI. This has led to the exploration of novel approaches to facilitate precision KI dosing, which have included model informed precision dosing based on integrated simulation/prediction platforms such as PK-Sim ® , GastroPlus TM , Phoenix TM , and Simcyp ® [ 26 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%